Pengaruh Penggunaan Smartphone Terhadap Komunikasi Generasi Z - Ananda Emellya (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2023)
Generation Z is more skilled in mastering information and technology. For generation Z, information technology such as smartphones is something that has become part of their lives, because this generation was born where access to information, especially through smartphones, has become a global culture. Therefore many children, teenagers and even adults are trapped in using smartphones. Budyatna said that with the use of smartphones, it has affected transactional processes, where often dynamic and reciprocal communication is felt to decrease in quality and quantity in direct interactions, this is influenced by the intensity of smartphone use. The intensity of using a smartphone is the level of frequency a person uses a smartphone based on pleasure from the activity. so that in the end those who are affected by the intensity of smartphone use tend to ignore the people around them and indirectly create bad ethics in direct socializing